The Use of Instagram and X Social Media in Managing Public Awareness of Viral Content in Indonesia - Savitri, Chelsea Gladies; Triyono, Agus (Universitas Dharmawangsa Medan, 2025)
In the digital age, social media has emerged as a dominant force in shaping public discourse. This research investigates how Instagram and X (formerly Twitter) are utilized to manage public awareness regarding viral content in Indonesia. Using a descriptive qualitative method, data were collected through in-depth interviews and digital observation of five viral cases spanning social, political, environmental, and cultural issues. The study applies Agenda Setting Theory and Public Communication Theory to analyze how each platform influences users’ perceptions. Findings show Instagram is effective in building emotional engagement through visual storytelling, while X serves as a dynamic forum for fast-paced opinion exchange. The contrast in platform characteristics influences how users interpret and respond to viral issues. The study concludes that while social media plays a significant role in shaping awareness, the impact varies depending on users’ digital literacy and critical engagement. The research highlights the need for media literacy in navigating complex information ecosystems and calls for responsible communication strategies in digital spaces.